The Boy Allies at Jutland; Or, The Greatest Naval Battle of History - Hayes, Clair W. (Clair Wallace), 1887- (Salt Lake City, UT : Project Gutenberg, 2003)
"The Boy Allies at Jutland; Or, The Greatest Naval Battle of History" by Ensign Robert L. Drake is a historical adventure novel written in the early 20th century, during the period of the First World War. The story follows two young officers, Frank Chadwick and Jack Templeton, who are aboard the British battleship H.M.S. "Queen Mary" as they prepare to re-enter active service and take part in one of history's most significant naval battles, the Battle of Jutland. The opening of the novel sets the stage for the impending conflict, introducing the massive battleship H.M.S. "Queen Mary" as it departs the Thames, full of anticipation and excitement among the crew. As the boys reflect on their past adventures under their former commander, Lord Hastings, they realize the critical role they now play in the upcoming battle. The initial chapters feature their conversations, the ship's preparations, and introduce various characters, hinting at the dangers that lie ahead for Frank and Jack as they navigate military life and the terrifying uncertainties of war. The vivid descriptions of naval warfare and the boys$1 (Bcamaraderie create a strong foundation for an exhilarating and action-packed narrative. (This is an automatically generated summary.)s
Release date is 2003-11-01
E-text prepared by Juliet Sutherland, Ginny Brewer, and Project Gutenberg Distributed Proofreaders
Keywords: World War, 1914-1918 -- Naval operations -- Juvenile fiction; Jutland, Battle of, 1916 -- Juvenile fiction